Barriers to HPV immunization among blacks and latinos: a qualitative analysis of caregivers, adolescents, and providers. (December 2016) - Katz, Ingrid; Bogart, Laura; Fu, Chong; Liu, Yingna; Cox, Joanne; Samuels, Ronald; Chase, Tami; Schubert, Pamela; Schuster, Mark
Abstract Background Despite recommendations that 11–12-year-olds receive the full three-shot Human papillomavirus (HPV) vaccine series, national HPV immunization coverage rates remain low. Disparities exist, with Blacks and Latinos being less likely than Whites to complete the series. We aimed to identify and compare barriers to HPV immunization perceived by healthcare providers, Black and Latino adolescents, and their caregivers to inform a clinic-based intervention to improve immunization rates. Methods We conducted semi-structured interviews between March and July 2014 with Black and Latino adolescents (n = 24), their caregivers (n = 24), and nurses (n = 18), and 2 focus groups with 18 physicians recruited from two pediatric primary care clinics. Qualitative protocol topics included: general perceptions and attitudes towards vaccines; HPV knowledge; and perceived individual and systems-level barriers affecting vaccine initiation and completion. Results Themes were identified and organized by individual and systems-level barriers to HPV immunization. Adolescents and their caregivers, particularly Blacks, expressed concerns about HPV being an untested, "newer" vaccine. All families felt they needed more information on HPV and found it difficult to return for multiple visits to complete the vaccine series. Providers focused on challenges related to administering multiple vaccines simultaneously, and perceptions of parental reluctance to discuss sexually transmitted infections. Conclusions Optimizing HPV immunization rates may benefit from a multi-pronged approach to holistically address provider, structural, and individual barriers to care. Further research should examine strategies for providing multiple modalities of support for providers, including a routinized system of vaccine promotion and delivery, and for addressing families' concerns about vaccine safety and efficacy.